Charlotte Blensdorf MacJannet addressing a group of campers while in costume, ca. 1962 - MacJannet, Donald (Tufts Archival Research Center, 2005)
2x2 color slide; taken from MS024/007-073 - "Donald MacJannet slides from travel and camp"